2014
DOI: 10.1007/s10495-014-1001-4
|View full text |Cite|
|
Sign up to set email alerts
|

AGGF1 protects from myocardial ischemia/reperfusion injury by regulating myocardial apoptosis and angiogenesis

Abstract: Angiogenic factor with G patch and FHA domains 1 (AGGF1) is a newly identified proangiogenic protein, which plays an important role in vascular disease and angiogenesis. However, its role in myocardial ischemia/reperfusion (I/R) injury remains unknown. This study investigated whether AGGF1 is involved in the pathogenesis of mouse myocardial I/R injury and the underlying mechanisms. Wild-type (WT) C57BL/6 J mice were treated at 30 min prior to I/R injury with anti-AGGF1 neutralizing antibody (3 mg/kg) or recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…Enforced expression of AGGF1 enhances angiogenesis and increases the blood flow in ischemic hindlimbs in a mouse model [12]. A recent study has reported that AGGF1 protects from myocardial ischemia/reperfusion injury by reducing myocardial apoptosis and enhancing angiogenesis [17]. In addition to endothelial cells, some types of cancer cells (e.g., bladder urothelial cancer cells [18]) can express AGGF1.…”
Section: Discussionmentioning
confidence: 99%
“…Enforced expression of AGGF1 enhances angiogenesis and increases the blood flow in ischemic hindlimbs in a mouse model [12]. A recent study has reported that AGGF1 protects from myocardial ischemia/reperfusion injury by reducing myocardial apoptosis and enhancing angiogenesis [17]. In addition to endothelial cells, some types of cancer cells (e.g., bladder urothelial cancer cells [18]) can express AGGF1.…”
Section: Discussionmentioning
confidence: 99%
“…Because the MAPK kinase [1,6] and PI3K/Akt [46] pathways play crucial roles in I/Rmediated signaling, we next examined the involvement of these pathways in the I/R-mediated induction of MCPIP1. First, we examined the effect of I/R on the activation of MAPKs.…”
Section: I/r-mediated Activation Of the Mapk (Erk Jnk P38) And Pi3kmentioning
confidence: 99%
“…Cardiovascular disease is the leading cause of death in advanced and industrialized countries; ischemia/reperfusion (I/R) injury is an important aspect of cardiovascular disease [1][2][3][4][5]. The prevention and management of I/R injury are key steps in coronary heart disease treatment and are becoming important issues in ischemic heart disease [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that myocardial apoptosis is an important aspect of myocardial I/R injury, which has been widely recognized (Huang et al, 2015; Liu et al, 2014; Sodha et al, 2008). Previous investigations indicated that activated JAK2 and STAT3 are sufficient to protect the myocardium against apoptosis (Jiang et al, 2015; Tian et al, 2011).…”
Section: Discussionmentioning
confidence: 99%